An experiment for a quality education using business materials tailored to learning profiles - Baraibar-Diez, Elisa; Odriozola, María D; Llorente García, Ignacio; Gómez López, Raquel; Luna Sotorrio, Ladislao (Journal of Management and Business Education, 2023)
With innovation serving as the primary driver, higher education institutions are essential to fulfilling the Sustainable Development Goal of quality education. Innovating in teaching means constantly adapting to new learning environments and changing audiences, but the advantage is that diversity remains constant. Making resources accessible in a variety of formats promotes inclusiveness, quality and flexibility to different learning preferences and styles, which supports a culture of lifelong learning. In a resource-constrained environment, lecturers often do not have evidence of how this variety of materials benefits the learner. A teaching innovation project is proposed to find out the diversity in learning styles in the classroom as well as the preferences and evaluations of students about three types of materials provided by lecturers of a given lesson, presented through text, graphics and audio. The results have given us a better understanding of the teaching-learning process and the needs of students.